Effects of the interactions between platelets with other cells in tumor growth and progression - Li, Yaxin; Wang, Haiyan; Zhao, Zhen; Yang, Yuanming; Meng, Zifan; Qin, Lifeng (Frontiers in Immunology, 2023)
It has been confirmed that platelets play a key role in tumorigenesis. Tumor-activated platelets can recruit blood cells and immune cells to migrate, establish an inflammatory tumor microenvironment at the sites of primary and metastatic tumors. On the other hand, they can also promote the differentiation of mesenchymal cells, which can accelerate the proliferation, genesis and migration of blood vessels. Besides, dendritic cells, natural killer cells, monocytes and erythrocytes are all proved to play an important part in the tumor microenvironment. As a result, it is obvious that tumorigenesis can be both influenced by the above-mentioned inflammation promotion and immunosuppressive effects. In this review, we summarize the major cells that are closely associated with tumor development and discuss the essential role of platelets in tumorigenesis and tumor development.